Are risk estimates biased in follow-up studies of psychosocial factors with low base-line participation? - Andersen Johan; Mikkelsen Sigurd; Rugulies Reiner; Kærgaard Anette; Thomsen Jane; Hansen Åse; Kolstad Henrik A; Kaerlev Linda; Mors Ole; Grynderup Matias B; Bonde Jens (BMC, 2011)
Abstract Background Low participation in population-based follow-up studies addressing psychosocial risk factors may cause biased estimation of health risk but the issue has seldom been examined. We compared risk estimates for selected health outcomes among respondents and the entire source population. Methods In a Danish cohort study of associations between psychosocial characteristics of the work environment and mental health, the source population of public service workers comprised 10,036 employees in 502 work units of which 4,489 participated (participation rate 45%). Data on the psychosocial work environment were obtained for each work unit by calculating the average of the employee self-reports. The average values were assigned all employees and non-respondent at the work unit. Outcome data on sick leave and prescription of antidepressant medication during the follow-up period (1.4.2007-31.12.2008) was obtained by linkage to national registries. Results Respondents differed at baseline from non-respondents by gender, age, employment status, sick leave and hospitalization for affective disorders. However, risk estimates for sick leave and prescription of antidepressant medication, during follow-up, based on the subset of participants, did only differ marginally from risk estimates based upon the entire population. Conclusions We found no indications that low participation at baseline distorts the estimates of associations between the work unit level of psychosocial work environment and mental health outcomes during follow-up. These results may not be valid for other exposures or outcomes.